2004
DOI: 10.1161/01.atv.0000137387.78515.61
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Genomic DNA, cDNA, and Nucleotide Sequence of the Mature C-Type Natriuretic Peptide Gene in Vascular Cells

Abstract: Objective-The aim of this study was to investigate the effect of various C-type natriuretic peptide (CNP) sequences (genomic DNA [CNPDNA], cDNA derived from mRNA [CNPcDNA], and sequence coding for 22 amino acids of the mature CNP [CNP22aa]) on the growth of primary porcine vascular cells. Methods and Results-Gene transfer was performed with cationic lipid DOCSPER or linear polyethylenimine. All 3 CNP sequences led to significant inhibition of smooth muscle cell (SMC) proliferation. In contrast, significant sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…For flow cytometric analysis, proliferating SMCs were seeded into 12-well plates and cultivated as previously described [9, 14, 22]. Transfection with Cy5-labelled (excitation at 650 nm, emission at 670 nm) plasmid DNA (Mirus Bio Corporation, Madison, Wisc., USA), unlabelled sPLLs and DOCSPER was done as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For flow cytometric analysis, proliferating SMCs were seeded into 12-well plates and cultivated as previously described [9, 14, 22]. Transfection with Cy5-labelled (excitation at 650 nm, emission at 670 nm) plasmid DNA (Mirus Bio Corporation, Madison, Wisc., USA), unlabelled sPLLs and DOCSPER was done as described above.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that perivascular events significantly affect neointima: adventitial irritation results in focal intimal thickening and markers applied to the adventitia can be visualized in the intima [7, 8]. Therefore, vascular SMCs may be a suitable target using adventitial deposition of gene therapy vectors [3, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, CNP binds NPR3 and in turn deactivates protein kinase A by G i -protein dependent inhibition of adenylate cyclase [3]. CNP has anti-proliferative and anti-migratory properties [4] and was also identified as an endothelium derived relaxing factor [5]. Furthermore, CNP inhibits neointimal restenosis, reduces vascular constrictive remodeling and cardiac ischemia-reperfusion injury [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…CNP plays an important role in bone growth [15,16], reproduction [17,18], nerve growth [19], re-endothelialisation [20], as well as renal [21], pancreatic [22], and cardiac function [23]. In addition, CNP has anti-proliferative and anti-migratory properties [11,24,25] and was also identified as an endothelium derived relaxing factor [26][27][28]. CNP stimulates selectively the human natriuretic peptide receptor 2 (NPR2), which in turn activates the cGMP-dependent kinase (cGK) by elevating intracellular level of cGMP [14].…”
Section: Introductionmentioning
confidence: 99%